Assessing the activity pattern overlap among leopards (Panthera pardus), potential prey and competitors in a complex landscape in Tanzania. (12th March 2020) - Havmøller, R. W.; Jacobsen, N. S.; Scharff, N.; Rovero, F.; Zimmermann, F.
Abstract: Studying activity patterns and temporal overlap among carnivores and their putative prey is difficult because of their secretive and elusive nature. With large carnivores declining worldwide, it is imperative for conservation planning that we understand how large carnivores interact with their prey and competitors. Camera trapping offers a promising avenue to address this issue. We investigated temporal overlap between male and female leopards, their known and putative prey as well as their competitor, the spotted hyenas, in the Udzungwa Mountains of Tanzania. Data consisted of 4297 independent events from a 30 min interval criterion from 164 camera trap sites we sampled. Leopards were captured by camera traps throughout the day, with male and female leopards showing significantly different activity patterns ( P  < 0.001) indicating sexual segregation in activity patterns, with male leopards being more nocturnal than female leopards. Leopards had significantly different activity patterns from that of the majority of their prey, with yellow baboons, that displayed peak activity during midday, that had the least overlap. Moreover, both male and female leopards had significantly different activity patterns from that of spotted hyenas ( P  = <0.001), with female leopards appearing to be inactive during hours with peak hyena activity. We conclude that systematic camera trapping is a useful tool to study activity patterns and temporal niche interactions between sympatric carnivores and, to a lesser extent, their prey. Abstract : Studying activity pattern overlap among carnivores, and their prey is difficult because of their secretive nature. Using camera traps, we investigated temporal overlap between male and female leopards, their prey as well as their competitor, the spotted hyena. Leopards were found to be cathemeral, with male and female leopards showing significantly different activity patterns from each other and also significantly different activity patterns from those of the majority of their prey. Moreover, both male and female leopards had significantly different activity patterns from those of spotted hyenas, with female leopards appearing to be inactive during the hours with peak hyena activity. We conclude that systematic camera trapping is a useful tool to study activity patterns and temporal niche interactions between sympatric carnivores and, to a lesser extent, their prey.